ANALYSIS OF LEAF TOLERANCE TO MIDVEIN DAMAGE BY A SIMPLE MIDVEIN CUT-OFF TRIAL - W. L. Fu; D. Y. Li; Y. Cao; 3; W. Li (Journal of Animal and Plant Sciences, 2020)
Venation type is an important trait for terrestrial plant leaves. Especially the midvein plays a crucial role in water and nutrient transportation and correlates with leaf tolerance to physical damage. In our study, we explored the leaf tolerance to midvein damages in 95 terrestrial species by a simple midvein cut-off trial. Within three months, no detectable changes of leaf intactness were found for over two-thirds of the selected species. In two species, Acer rubrum and Hylotelephium erythrostictum, over 10 % of the leaf area was damaged by the end of the experiment. The diameter of the midvein and the leaf length showed a significantly positive correlation with the ratio of lamina damaged area to the total area (RLD), but the correlation became insignificant after including the phylogenetic relationships. The RLD varied considerably within each venation type (netted or parallel) while showed no significant difference and did not differ significantly between the two venation types; however, the RLD tended to be higher in herbaceous plants than in shrubs and trees. Our results indicated that the leaf tolerance to physical damages on the midvein of terrestrial plants was a trait somehow independent of phylogenetic relationships.
Keywords: terrestrial plants; Acer rubrum; Hylotelephium erythrostictum; midvein damage; leaf tolerance; venation type